# Difference between revisions of "99 questions/Solutions/7"

< 99 questions | Solutions

Jump to navigation
Jump to search
(Some additional solutions for this question) |
(Add an implementation using -XDeriveFoldable) |
||

(7 intermediate revisions by 5 users not shown) | |||

Line 14: | Line 14: | ||

flatten (List (x:xs)) = flatten x ++ flatten (List xs) |
flatten (List (x:xs)) = flatten x ++ flatten (List xs) |
||

flatten (List []) = [] |
flatten (List []) = [] |
||

+ | </haskell> |
||

+ | or using things that act just like <hask>concatMap</hask> |
||

+ | <haskell> |
||

+ | flatten (Elem x) = return x |
||

+ | flatten (List x) = flatten =<< x |
||

+ | |||

+ | flatten (Elem x) = [x] |
||

+ | flatten (List x) = foldMap flatten x |
||

</haskell> |
</haskell> |
||

<haskell> |
<haskell> |
||

Line 21: | Line 29: | ||

flt' (List (x:ls)) xs = flt' x (flt' (List ls) xs) |
flt' (List (x:ls)) xs = flt' x (flt' (List ls) xs) |
||

flt' (List []) xs = xs |
flt' (List []) xs = xs |
||

+ | </haskell> |
||

+ | or with foldr |
||

+ | <haskell> |
||

+ | flatten3 :: NestedList a -> [a] |
||

+ | flatten3 (Elem x ) = [x] |
||

+ | flatten3 (List xs) = foldr (++) [] $ map flatten3 xs |
||

+ | </haskell> |
||

+ | |||

+ | or with an accumulator function: |
||

+ | <haskell> |
||

+ | flatten4 = reverse . rec [] |
||

+ | where |
||

+ | rec acc (List []) = acc |
||

+ | rec acc (Elem x) = x:acc |
||

+ | rec acc (List (x:xs)) = rec (rec acc x) (List xs) |
||

+ | </haskell> |
||

+ | |||

+ | or making NestedList an instance of Foldable: |
||

+ | <haskell> |
||

+ | import qualified Data.Foldable as F |
||

+ | instance F.Foldable NestedList where |
||

+ | foldMap f (Elem x) = f x |
||

+ | foldMap f (List []) = mempty |
||

+ | foldMap f (List (x:xs)) = F.foldMap f x `mappend` F.foldMap f (List xs) |
||

+ | |||

+ | flatten5 :: NestedList a -> [a] |
||

+ | flatten5 = F.foldMap (\x -> [x]) |
||

+ | </haskell> |
||

+ | or making use of -XDeriveFoldable: |
||

+ | <haskell> |
||

+ | {-# LANGUAGE DeriveFoldable #-} |
||

+ | |||

+ | import Data.Foldable |
||

+ | |||

+ | data NestedList a = Elem a | List [NestedList a] deriving Foldable |
||

+ | |||

+ | flatten6 :: NestedList a -> [a] |
||

+ | flatten6 = toList |
||

</haskell> |
</haskell> |
||

Line 29: | Line 75: | ||

Our NestedList datatype is either a single element of some type (Elem a), or a |
Our NestedList datatype is either a single element of some type (Elem a), or a |
||

list of NestedLists of the same type. (List [NestedList a]). |
list of NestedLists of the same type. (List [NestedList a]). |
||

+ | |||

+ | [[Category:Programming exercise spoilers]] |

## Latest revision as of 01:48, 13 July 2020

(**) Flatten a nested list structure.

```
data NestedList a = Elem a | List [NestedList a]
flatten :: NestedList a -> [a]
flatten (Elem x) = [x]
flatten (List x) = concatMap flatten x
```

or without concatMap

```
flatten :: NestedList a -> [a]
flatten (Elem a ) = [a]
flatten (List (x:xs)) = flatten x ++ flatten (List xs)
flatten (List []) = []
```

or using things that act just like `concatMap`

```
flatten (Elem x) = return x
flatten (List x) = flatten =<< x
flatten (Elem x) = [x]
flatten (List x) = foldMap flatten x
```

```
flatten2 :: NestedList a -> [a]
flatten2 a = flt' a []
where flt' (Elem x) xs = x:xs
flt' (List (x:ls)) xs = flt' x (flt' (List ls) xs)
flt' (List []) xs = xs
```

or with foldr

```
flatten3 :: NestedList a -> [a]
flatten3 (Elem x ) = [x]
flatten3 (List xs) = foldr (++) [] $ map flatten3 xs
```

or with an accumulator function:

```
flatten4 = reverse . rec []
where
rec acc (List []) = acc
rec acc (Elem x) = x:acc
rec acc (List (x:xs)) = rec (rec acc x) (List xs)
```

or making NestedList an instance of Foldable:

```
import qualified Data.Foldable as F
instance F.Foldable NestedList where
foldMap f (Elem x) = f x
foldMap f (List []) = mempty
foldMap f (List (x:xs)) = F.foldMap f x `mappend` F.foldMap f (List xs)
flatten5 :: NestedList a -> [a]
flatten5 = F.foldMap (\x -> [x])
```

or making use of -XDeriveFoldable:

```
{-# LANGUAGE DeriveFoldable #-}
import Data.Foldable
data NestedList a = Elem a | List [NestedList a] deriving Foldable
flatten6 :: NestedList a -> [a]
flatten6 = toList
```

We have to define a new data type, because lists in Haskell are homogeneous. [1, [2, [3, 4], 5]] is a type error. Therefore, we must have a way of representing a list that may (or may not) be nested.

Our NestedList datatype is either a single element of some type (Elem a), or a list of NestedLists of the same type. (List [NestedList a]).